An Oxygen Transport Model of Human Bone Marrow for Hemolytic Sickle Cell Anemia (Journal of Chemical Engineering, 2010)
The human bone marrow (BM) is a complicated tissue with intricate vascular and heterogeneousextravascular (tissue) architecture. Oxygen is an important modulator of differentiation and proliferationof the BM hematopoietic cells under normal and pathological conditions. Currently, due to theinaccessibility of the BM, it is not possible to measure the spatial distribution of the oxygen tension(concentration) levels in the tissue. Thus, the present treatise utilizes mathematical modeling to offer agreater insight on the effects of oxygen on the BM cellular components. Here, we present simulationresults that are correlated with known in vivo data of BM along with proposing a model for the two statedescription of allosteric hemoglobin molecule under hemolytic sickle cell anemia condition of BM.Journal of Chemical Engineering Vol.ChE 24 2006 7-13